Are Island Allowed to Announce Continental Sea Shelves or EEZ in the Eastern Mediterranean? Turkey-Greece Dispute - Dostel, Kemal (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2021)
The political and international disputes regarding recognition of EEZ and Continental Sea Shelves around islands have been a long discussion point throughout history. However, the importance of these islands and the EEZ are increasing which results in geopolitical disputes and maximalist claims of Greece in the Eastern Mediterranean Continental Sea Shelves leading to major friction between two neighbouring countries, namely Turkey and Greece. After the discovery of hydrocarbon resources around the offshore North and South Cyprus, the problem of EEZ and Continental Sea Shelves around the Mediterranean Sea has led to an increasing geopolitical issue. In this study, the topic will be discussed thoroughly with respect to the rights of islands in the scope of EEZ and Continental Sea Shelves. Economic benefits and commercialization of gas in the future will be investigated with different scenario analysis.

ÖZ: Adalar çevresinde münhasır ekonomik bölge ve kıta deniz sahanlıklarının tanınmasına ilişkin siyasi ve uluslararası anlaşmazlıklar tarih boyunca uzun bir tartışma konusu olmuştur. Ancak adaların ve münhasır ekonomik bölgenin önemi artmakta ve bu da Yunanistan'ın Doğu Akdeniz Kıta Deniz Sahanlığı'ndaki jeopolitik anlaşmazlıkları ve maksimalist iddiaları ile sonuçlanarak iki komşu ülke, yani Türkiye ve Yunanistan arasında büyük sürtüşmelere yol açmaktadır. Kuzey ve Güney Kıbrıs açıklarında hidrokarbon kaynaklarının keşfinden sonra, Akdeniz çevresindeki münhasır ekonomik bölge ve kıta deniz sahanlıkları sorunu artan bir jeopolitik soruna yol açmıştır. Bu çalışmada, adaların münhasır ekonomik bölge ve kıta deniz sahanlıkları kapsamındaki hakları tartisilacaktir. Farklı senaryo analizleri ile ileriki yillarda gazın ekonomik faydaları ve ticarileşmesi araştırılacaktır
Master of Science in Economics. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Economics, 2021. Supervisor: Prof. Dr. Vedat Yorucu.
Keywords: Thesis Tez; Economics Department; Natural gas--Economics--Cyprus--Turkey--Greece; Natural gas--Economic aspects--Cyprus; Gas industry; Petroleum--resource economics; Energy Economics--Mediterranean Region; Political Relations--Diplomacy--Dispute--Turkey--Greece; Exclusive Economic Zone (EEZ)